Understanding Factors Affecting Inclusions of Students with Disabilities in Higher Education: A Study among Non-Disabled University Students - Saadun, Saadiah Juliana; Ab Latiff, Dilla Shadia; Mohamed Besir, Mohamad Shahril; Alias, Roslinda; Fikri, Mohd Faris; Imran Nanang, Jazmin Qistina binti (Information Management and Business Review, 2024)
Inclusive education for people with disabilities is gaining importance globally, with improving factors that support the inclusion of students with disabilities in higher education as a key objective. This study explores how societal and environmental factors shape perceptions of disability, rather than viewing it solely as an individual limitation. A non-probability convenience sampling method was employed, involving 279 university students from six different faculties. Data were analyzed through frequency distribution and SPSS to examine the attitudes of non-disabled students toward the inclusion of their disabled peers in higher education. The findings reveal that environmental barriers are strongly associated with the attitudes of non-disabled students toward their peers with disabilities (r = .693, p < .01), indicating that these barriers significantly impact how students perceive and interact with those who have impairments. The non-disabled students identified specific environmental factors that either support or hinder the inclusion of disabled students in university settings. This research highlights the need for addressing environmental obstacles to foster a more inclusive and supportive educational environment for all students.